A mathematical model of the Purkinje-Muscle Junctions - Adnane Azzouzi; Yves Coudière; Rodolphe Turpault; Nejib Zemzemi (Mathematical Biosciences and Engineering)
This paper is devoted to the construction of a mathematical model of the His-Purkinje tree and the Purkinje-Muscle Junctions (PMJ). A simple numerical scheme is proposed in order to perform some simple numerical experiments.